The effect of different extenders on post-thaw sperm survival, acrosomal integrity and longevity in cryopreserved semen of Formosan Sika deer and Formosan Sambar deer - Cheng, Feng-Pang; Wu, Jui-Te; Chan, Jacky Peng-Wen; Wang, Jiunn-Shiow; Fung, Hang-Poung; Colenbrander, Ben; Tung, Kwong-Chung (Theriogenology, 2004)
This study investigates the efficacy of five extenders in contributing to the outcome of semen cryopreservation in Formosan Sika and Sambar deer. Pooled semen ( n=4) of six males of each breed was used. In Sika deer, semen collection rate was 96% (23/24) over all electro-ejaculations. Volume, sperm motility and sperm concentration of fresh ejaculates was 0.5±0.4 ml, 77±6% and 1471.3±940.0×10 6 ml −1, respectively. Post-thaw motility in respective extender was A: 66±16%; B: 71±2%; C: 73±6%; D: 9±4% and E: 26±12% (mean±S.D.). In extender C (74±14%) more viable spermatozoa were preserved than in the others (A: 64±10%; B: 48±11%; D: 41±16%; E: 47±6%; P<0.05). Acrosomal integrity was not influenced by extender composition. Post-thaw motility did not decrease during a 4-h incubation period, irrespective of the extender used ( P>0.05). In Sambar deer, semen collection rate was 88% (21/24) over all electro-ejaculations. Volume, sperm motility and sperm concentration of fresh ejaculates was 1.3±0.5 ml, 82±4% and 379.1±252.2×10 6 ml −1, respectively. Post-thaw motility was in respective extenders A: 69±2%; B: 74±6%; C: 73±2%; D: 13±6% and E: 31±20%. Extenders B and C were superior ( P>0.05) with respect to sperm motility. Similarly, post-thaw viability in extenders A (70±7%), B (76±7%) and C (79±2%) was higher than that D (25±19%) and E (29±17%) ( P<0.01). Sperm acrosomal integrity was better preserved in extenders B (86±4%) and C (83±4%) than in extenders A (54±13%), D (39±22%) and E (46±22%) ( P<0.05). Post-thaw sperm longevity in extender A reduced from 69 to 16% during incubation ( P<0.05) whereas only a slight decrease was observed in the other extenders after 4 h. In conclusion these data show that egg-yolk–Tris–Tes–glycerol based extender C containing Equex STM paste is optimal for freezing semen of Formosan Sika deer while egg-yolk–Tris–citric acid–glycerol based extender B containing Equex and extender C are superior in semen cryopreservation to others for Formosan Sambar deer.